Excitation Density Dependent Photoluminescence Quenching and Charge Transfer Efficiencies in Hybrid Perovskite/Organic Semiconductor Bilayers. Issue 35 (23rd October 2018) - Kim, Jinhyun; Godin, Robert; Dimitrov, Stoichko D.; Du, Tian; Bryant, Daniel; McLachlan, Martyn A.; Durrant, James R.
Abstract: This study addresses the dependence of charge transfer efficiency between bilayers of methylammonium lead iodide (MAPI3 ) with PC61 BM or poly(3, 4‐ethylenedioxythiophene): polystyrene sulfonate (PEDOT:PSS) charge transfer layers on excitation intensity. It analyzes the kinetic competition between interfacial electron/hole transfer and charge trapping and recombination within MAPI3 by employing a range of optical measurements including steady‐state (SS) photoluminescence quenching (PLQ), and transient photoluminescence and absorption over a broad range of excitation densities. The results indicate that PLQ measurements with a typical photoluminescence spectrometer can yield significantly different transfer efficiencies to those measured under 1 Sun irradiation. Steady‐state and pulsed measurements indicate low transfer efficiencies at low excitation conditions (<5E + 15 cm −3 ) due to rapid charge trapping and low transfer efficiencies at high excitation conditions (>5E + 17 cm −3 ) due to fast bimolecular recombination. Efficient transfer to PC61 BM or PEDOT:PSS is only observed under intermediate excitation conditions (≈1 Sun irradiation) where electron and hole transfer times are determined to be 36 and 11 ns, respectively. The results are discussed in terms of their relevance to the excitation density dependence of device photocurrent generation, impact of charge trapping on this dependence, and appropriate methodologies to determine charge transfer efficiencies relevant to device performance. Abstract : The light intensity dependence of interfacial charge transfer efficiency in methylammonium lead iodide (MAPI3 ) perovskite bilayers with electron/hole transfer layers is investigated using a range of steady‐state and time‐resolved optical techniques, allowing quantification of the kinetic competition between charge transfer versus recombination and trapping under irradiation conditions relevant to device operation.